Perceived Stress Mediates the Relationship of Body Image and Depressive Symptoms in Individuals With Obesity - Ziser, Katrin; Finklenburg, Carina; Behrens, Simone Claire; Giel, Katrin Elisabeth; Becker, Sandra; Skoda, Eva-Maria; Teufel, Martin; Mack, Isabelle; Zipfel, Stephan; Junne, Florian (Frontiers in Psychiatry, 2019)
Obesity is a world-wide increasing condition classified by a BMI ≥ 30 kg/m2 that is frequently accompanied by various somatic comorbidities as well as an increased risk for mental comorbidities. Studies show associations of obesity with symptoms of depression, lower quality of life and higher (perceived) stress compared to the general population. Body image has also been shown to play an important role in eating and weight disorders. The present study therefore aims to contribute to the understanding of the relationship of body image, perceived stress and symptoms of depression in a morbidly obese population. N = 579 individuals with obesity were included upon presentation at a university clinic. The hypothesized mediating role of perceived stress in the relationship of body image dimensions and symptoms of depression could be confirmed. The results underline the importance of identifying promising stress management techniques and addressing perceived stress e.g. through mindfulness based approaches in the (lifestyle and/or weight) interventions for obesity taking into account the specific stressors of obesity affected individuals such as body image.